1990
DOI: 10.3133/ofr89402
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeologic reconnaissance of the Swope Oil Superfund site and vicinity, Camden and Burlington counties, New Jersey

Abstract: From 1965-79, a chemical reclamation facility, now known as the Swope Oil Superfund site, sold and processed a variety of chemical compounds. Operation of the facility resulted in contamination of ground water beneath the 1.9-acre site. During 1984, the maximum concentrations of chromium and lead in ground water were 64 and 90 jug/L (micrograms per liter), respectively; the maximum concentration of total purgeable organic compounds (POCs) was 108 jug/L; and the maximum concentration of total base/neutraland ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some additional commercial and industrial supply wells screened in the Potomac-Raritan-Magothy aquifers are present in the study area. Ground-water contaminants are not confined to the area of the Puchack well field; VOCs were detected at some of the Merchantville-Pennsauken Water Supply Commissions wells at the Park Avenue and National Highway well fields as early as 1980 (Barton and Krebs, 1990).…”
Section: Description Of Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Some additional commercial and industrial supply wells screened in the Potomac-Raritan-Magothy aquifers are present in the study area. Ground-water contaminants are not confined to the area of the Puchack well field; VOCs were detected at some of the Merchantville-Pennsauken Water Supply Commissions wells at the Park Avenue and National Highway well fields as early as 1980 (Barton and Krebs, 1990).…”
Section: Description Of Study Areamentioning
confidence: 99%
“…They found that VOC contamination was detected most commonly in the Lower Potomac-Raritan-Magothy aquifer in and near the outcrop area, and concluded that the presence of VOCs was the result of human activities in the extensive urbanized areas overlying the outcrops. Barton and Krebs (1990) compiled geochemical, geohydrologic, and geophysical data from wells and boreholes in the vicinity of the Swope Oil Superfund site in Pennsauken Township.…”
Section: Hydrogeologic Settingmentioning
confidence: 99%